Safety Evaluation and Risk Assessment for Treated Water Pipe Replacement Fabrication, Installation and Dismantling Process - Othman Lutifi, Ali Lutifi; Syahrun Neizam Mohd Dzulkifli; Atikah Mustaffa (Progress in Engineering Application and Technology, 2023)
This study was conducted on a fabrication or maintenance company for the oil and gas industry. The objective of the study is to identify the hazards, assess and evaluate the risks that exist during pipe work and related activities. Next, control measures will be proposed to ensure that the risk of harm is reduced. For that, several methods have been implemented to obtain the information needed to achieve the objective. Visits to the workplace are carried out to obtain clearer information about the plumbing process as well as to see more clearly the dangers in the workplace. Next, existing control measures can be recorded for the risk assessment process. As a result of the assessment, the level of risk can be determined. Based on the research conducted on this assessment, JHA is more effective than HIRARC. HIRARC is for all routine work or processes in the workplace while JHA is used for non-routine work. Through this method, the dangers found in the workplace can be divided according to the level of the type of danger whether physical, chemical, ergonomic and electrical. The results of this study can identify possible or potential hazards during the process. Analyzes hazard levels for activities and recommends improvements to reduce hazards. Employee commitment and support from company management is essential to creating and succeeding in a healthier and safer workplace.